Factors influencing the overall satisfaction of teachers participating in a nationwide school-based smoking prevention program in Korea - Geon Heo; Seulgi Kim; Sung-il Cho; Seunghyun Yoo; Jieun Hwang (Tobacco Induced Diseases, 2024)
Introduction Numerous studies of school-based smoking prevention programs (SSPPs) exist; however, most have been conducted from the students' perspective, and insufficient research has explored teachers' perceptions. Our study aimed to identify factors affecting overall satisfaction and operational status from the perspective of teachers participating in the SSPP.